Pengembangan Sistem Informasi E-Complaint (Studi Kasus GraPARI Telkomsel Malang) - Muhammad Adnan; Retno Indah Rokhmawati; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
One of the goals GraPARI Telkomsel Malang is to provide services in handling customer complaints. Acceptance of complaints can be done in several ways, including through My GraPARI machine, call center and come directly to GraPARI office. Acceptance of customer complaints through My GraPARI machine or through the call center is considered not meet the needs, given the limited number of My GraPARI machines available only one unit in the city of Malang. As for the handling of complaints that require further handling, call center is considered not able to handle maximally because every process of handling must be informed directly to the customer. So to answer the above problems, can be given a solution of information system development as one form of application of the concept of Customer Relationship Management (CRM) Operational intended to receive complaints from customers. The method used in system development is using waterfall model which includes several stages of development, including: needs analysis, design, implementation and testing. System testing is done with several types of testing, including: black-box, compatibility, web service testing and system evaluation using the utility system approach. From the overall test results can be concluded that the features on the system has been running with a valid and can run on several type of browsers that have been tested.